Hepatozoon sp. gamonts as an accidental finding in synovial liquid from an injured maned wolf (Chrysocyon brachyurus) in southeastern Brazil - Perles, Lívia; Barranco, Guilherme Henrique Fernandes; Soriano, Isabela Maciel; Cruz, Nathan Da Rocha Neves; Bueno, Patrícia Jábali; Santana, Áureo Evangelista; Machado, Rosangela Zacarias; Werther, Karin; André, Marcos Rogério (Colégio Brasileiro de Parasitologia Veterinária, 2019)
Abstract A free-living, adult male maned wolf (Chrysocyon brachyurus) was referred to the Governador “Laudo Natel” – FCAV/Unesp veterinary hospital after being found with skin lesions and a fracture on the right pelvic limb, which had to be amputated due to compromised integrity. Around 20 days later, bilateral accentuated swollen on humerus-radius-ulna articulation was observed. The synovial liquid was drained and sent to the laboratory for synovial cytology with Rosenfeld staining that revealed predominantly degenerated neutrophils with karyolytic chromatin associated with intracellular inclusions suggestive of Hepatozoon sp. gametocytes. Blood and synovial liquid samples were submitted to molecular analysis, aiming to amplify the Hepatozoon spp. 18S rRNA gene fragment. Despite the positioning of the found Hepatozoon sequence together with Hepatozoon canis previously detected in domestic carnivores, the BLAST analysis showed only 98% identity with H. canis. To the best of the authors’ knowledge, this is the first time a Hepatozoon was detected in the synovial liquid by clinical pathology and molecular analyses.

Resumo Um lobo guará (Chrysocyon brachyurus) adulto, macho, de vida livre foi encaminhado para atendimento no hospital veterinário Governador “Laudo Natel” – FCAV/Unesp após ser encontrado com lesões de pele e fratura em membro pélvico direito, sendo amputado devido a comprometimento da integridade do membro. Aproximadamente 20 dias após a chegada ao hospital, foi notado acentuado aumento de volume bilateral em região de articulação úmero-rádio-ulnar. O líquido sinovial foi drenado e enviado para análise citológica com coloração de Rosenfeld, revelando a presença de neutrófilos degenerados com cromatina cariolítica associados a inclusões intracelulares sugestivas de gametócitos de Hepatozoon sp. Amostras de sangue e líquido sinovial foram submetidas a análises moleculares visando amplificar um fragmento do gene 18S rRNA de Hepatozoon spp. Apesar da sequência de Hepatozoon detectada se posicionar filogeneticamente no mesmo clado que H. canis previamente detectado em carnívoros domésticos, o resultado da análise do BLAST mostrou somente 98% de identidade com H. canis. De acordo com o conhecimento dos autores, esta é a primeira vez que Hepatozoon foi detectado no líquido sinovial por meio de patologia clínica e análises moleculares.
Gamontes de Hepatozoon sp. como achado acidental em líquido sinovial de lobo guará (Chrysocyon brachyurus) no sudeste do Brasil
Keywords: Hepatozoonosis; cytopathology; gametocytes; wild canids; Hepatozoonose; citopatologia; gametócitos; canídeos selvagens